PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PADA SISWA KELAS VIII DI MTS NUR ET-TAQWA CIKANDE - Nila Nurjanah; Jaka Wijaya Kusuma; Maulida Nur (LPPM Universitas Bina Bangsa, 2022)
The background in this study is the ability to understand mathematical concepts of students at MTs Nur Et-Taqwa Cikande is still low. This can be seen from the average score at the school is still below the KKM, which is 72, and the perspective of students in learning mathematics is not good and the learning model used is still a conventional learning model which makes students still passive or not active in learning. This study aims to determine whether the ability to understand mathematical concepts of students who are taught using generative learning is better than students who are taught using conventional learning and to find out how the influence of generative learning models on the ability to understand mathematical concepts. This research uses quantitative research with True Experimental Design method using pretest-posttest control group design type. The data collection technique used is the test. The data analysis used is normality test, homogeneity test, similarity test of two averages and effect size test. The population used was all eighth grade students at MTs Nur Et-Taqwa Cikande. This study used a total sampling technique, namely class VIII A with a total of 21 students as the experimental class and VIII B with a total of 20 students as the control class. Based on the similarity test of the two averages and the effect size test so that the results of the test of the difference between the two averages can be seen in the equal variance assumed section, the value tcount = 2.680 > 2.672 with a significant value of 0.011 < 0.05 so that H0 is rejected and Ha is accepted. While the test using the effect size is 0.85 with an interpretation of the effect size of 79% which is a high category